2006
DOI: 10.1021/jf0620057
|View full text |Cite
|
Sign up to set email alerts
|

Immunochromatography Using Colloidal Gold−Antibody Probe for the Detection of Atrazine in Water Samples

Abstract: An immunochromatography (ICG) strip test for rapid detection of atrazine in water samples was developed. A monoclonal antibody (MAb) specific to atrazine was produced from the cloned hybridoma cell (AT-1-M3) and used to develop a direct competitive enzyme-linked immunosorbent assay (DC-ELISA) and ICG strip. MAb conjugated to colloidal gold, and that was applied to the conjugate pad of the ICG strip. The visual detection limit for the ICG strip was 3 ng/mL. This test required only 10 min to get results and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 18 publications
(17 reference statements)
3
71
0
2
Order By: Relevance
“…Sample pads were treated according to Shim et al (27), with some modifications. Cellulose fiber sample pads (Millipore), 1.5 by 0.5 cm, were dipped into the sample pad buffer (50 mM borate buffer [pH 7.2], 5% sucrose, 0.5% Tween 20, 5% dextran, and 0.1% skim milk) and then dried at 50°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample pads were treated according to Shim et al (27), with some modifications. Cellulose fiber sample pads (Millipore), 1.5 by 0.5 cm, were dipped into the sample pad buffer (50 mM borate buffer [pH 7.2], 5% sucrose, 0.5% Tween 20, 5% dextran, and 0.1% skim milk) and then dried at 50°C.…”
Section: Methodsmentioning
confidence: 99%
“…(28), and the rrl gene (482 bp), which is specific for Leptospira genus (29). The primers used in this experiment were specific for the flaB gene (L-flaB-F1 [5=-TCTCACCGTTCTCTAAAGTTCAAC-3=] and L-flaB-R1 [5=-CTGAATTCGGTTTCATATTTGCC-3=]) (27) and for the rrl gene (rrlF [5=-GACCCGAAGCCTGTCGAG-3=] and rrlR [5=-GCCATGCTTAGTCCCGATTAC-3=]) (29) of Leptospira spp. flaB was amplified under the following conditions: 40 cycles of denaturing at 94°C for 20 s, annealing at 50°C for 30 s, extension at 72°C for 60 s, and final extension at 72°C for 5 min.…”
Section: Serratia Marcescens J1 J5mentioning
confidence: 99%
“…Some authors have successfully described LFDs for aflatoxins that work well with corn [18], grains and feedstuffs [25,26] and milk [27], but require strip treatment before use. A new LFD for aflatoxins that did not require special pre-treatment was developed by Masinde et al [19] and has been commercialised as the Aflatoxin Quicktest™ by QuickTest Technologies.…”
Section: Poisoning -From Specific Toxic Agents To Novel Rapid and Simmentioning
confidence: 99%
“…It was reported that Helicobacter pylori in the urine was detected using an immunochromatographic assay (Graham and Reddy, 2001). Atrazine in water samples (Shim et al, 2006) and theophylline enzyme in whole blood samples were also detected by an immunochromatographic method (Habib et al, 1987). Bikker et al (2007) reported the detection of sulfur mustard adducts in human callus by phage antibodies.…”
Section: Specificity Study Of Laminin-5 γ γ γ γ γ 2 Degradation Usingmentioning
confidence: 99%